Meningkatkan pembangunan reaktor nuklir: Menjamin kesehatan di seluruh dunia - Cahyani, Nadilah Dwi (Maliki Interdisciplinary Journal, 2025)
Nuclear reactors have great potential in providing sustainable, stable, and environmentally friendly energy. Using uranium fuel can produce large amounts of energy with minimal carbon emissions, and help reduce the impact of climate change. In addition to being used for energy, nuclear technology is also useful in the medical field, especially in the diagnosis and therapy of diseases through the use of radioisotopes, and in the sterilization of medical devices. However, nuclear reactor technology has dangerous risks, such as radiation leaks that can have adverse effects on health and the environment. Therefore, nuclear reactors are equipped with various safety systems, including emergency cooling, containment vessels, and strict radiation monitoring protocols. International safety standards from agencies such as the IAEA must be followed, and education for the public is needed so that they understand how to deal with possible risks. Cooperation with world health organizations is needed to socialize the benefits of nuclear, in order to increase public confidence in nuclear energy as a sustainable energy solution in the future.